Dampak Anestesi Umum, Spinal dan Epidural Terhadap Tempat Rawat Pasca Operasi dan Skor Apgar pada Pasien Preeklampsia Berat yang Dilakukan Seksiosesaria di RSUP Dr Sardjito Tahun 2004-2006 - Pramono, Ardi; Uyun, Yusmein; Suryono, Bambang (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2008)
The author want to know the place of post operative care and Apgar score of general and regional anesthesia in patients with severe preeclampsia who will be performed sectiosecaria in Sardjito Hospital Yogyakarta year 2004-2006. Data will be collected from medical record. The study will be conducted with cohort retrospective and sample method with consequtive sampling. The inclusion criteria of severe preeclampsia patients were systolic pressure e â€ 160mmHg and or diastolic pressure e " llOmmHg before any medical intervention with one or more sign of protein-uria, visual disturbance during pregnancy, and cyanosis, without any disseminated intravascular coagulation (DIC), pulmonary edema, organ dysfunction, and HELLP (hemolytic, elevated liver enzyme, low platelet) syndrome. The recovery room of post operative care was divided into standard room, intensive care unit (ICU) with or without mechanical ventilator. General anesthesia will be limited using tiopenthal as induction agent, and regional anesthesia technique (spinal or epidural) with bupivacain. The result showed that there were no differences in recovery room of post operative care between general, spinal, and regional anesthesia (p 0.05). Apgar score in first 1 minute was significant lower in general compared with spinal and epidural anesthesia.